Dampak Paradigma Baru Terhadap Pengembangan Media dan Metode Pembelajaran PAI di MA Nurul Islam Kota Sukabumi - Azazi, Abdul Kohar; Nugraha, Mulyawan Safwandy (CV. Berkah Cakrawala Inspirasi, 2026)
This study examines the impact of the new paradigm on the development of instructional media and teaching methods in Islamic Religious Education at MA Nurul Islam, Sukabumi City. Using a qualitative case study design, data were collected through document analysis, classroom observations, and semi-structured interviews with students, the Islamic Religious Education teacher, and the principal. The analysis indicates that the school has established supportive conditions through academic supervision and an internal MGMP forum that encourages innovation and reflective practice. The most visible impact appears in the increased use of digital media, including PowerPoint, projectors, and interactive platforms for formative assessment. Changes in teaching methods are emerging through contextual prompts, group discussions, and project-based learning activities, yet implementation remains inconsistent across classes. Student participation and critical engagement vary, and collaboration is not uniformly developed. Assessment practices show a gradual shift toward formative and digital approaches; however, traditional one-way evaluation and memorization-based tasks persist in some lessons. The key challenges include unequal teacher readiness, limited facilities, and the need for stronger digital source literacy, including guidance on responsible AI use. These findings suggest that media innovation progresses faster than pedagogical and assessment transformation, requiring targeted capacity building and clearer classroom-level standards.